Consumption of a Probiotic Blend with Vitamin D Improves Immunity, Redox, and Inflammatory State, Decreasing the Rate of Aging—A Pilot Study - Judith Félix; Adriana Baca; Luz Taboada; Guillermo Álvarez-Calatayud; Mónica De la Fuente (Biomolecules)
There is evidence of the effect of probiotic intake on the immune system. However, the effect probiotics may have on the rate of aging is unknown. The aim of this study is to determine the effect of a probiotic blend on immunity, redox state, inflammation, and the rate of aging or biological age. A group of 10 men and 14 women took, daily for 2 months, a sachet with three probiotics (Bifidobacterium animalis subsp. lactis BSO1, Lactobacillus reuteri LRE02, Lactobacillus plantarum LP14) and vitamin D. Before starting the treatment and after 2 months, peripheral blood was collected. Immune functions were assessed in isolated immune cells, and cytokine concentrations were also measured both in mononuclear cell cultures and plasma. Redox state parameters were also analyzed in whole blood cells. Finally, the Immunity Clock was applied to determine the biological age. Results show that the intake of this probiotic blend in general, in both men and women, improves immunity and decreases the oxidative and inflammatory state. In addition, it rejuvenates the biological age by 10 years on average. It can be concluded that this probiotic blend could be proposed as a good strategy to slow down the aging process, and to achieve healthy aging.